Exploring The Challenges Faced BY Teachers In Teaching English Reading Skills To Grade VIII Student At SMPN 14 Kaur - Dia Santika, Elsa; Rizal, Syamsul; Febriani, Hanura (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to explore the challenges faced by English teachers in teaching reading skills to Grade VIII students at SMPN 14 Kaur. Specifically, it identified the strategies used by the teacher, the challenges encountered during the implementation of those strategies, and the solutions applied to overcome them. This study employed a qualitative case study design. The participants consisted of one English teacher and eight Grade VIII students. Data were collected through semi-structured interviews, classroom observations, questionnaires, open-ended questions, and documentation. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. Data triangulation was used to ensure the trustworthiness of the findings. The findings showed that the teacher used reading aloud, question-and-answer sessions, vocabulary explanation, translation, and rewards to develop students' reading skills. The main challenges were students' limited vocabulary, low interest in reading, pronunciation difficulties, limited instructional time, and different reading abilities. To overcome these challenges, the teacher simplified the learning materials, explained vocabulary before reading activities, encouraged students to use dictionaries, provided additional guidance, and motivated students through praise and rewards. The study concluded that appropriate teaching strategies and continuous support are important for improving students' reading skills.